Antifungal protein determination for submerged cultures of the medicinal mushroom Ganoderma lucidum (Ganodermataceae) with activity over the phytopathogen fungus Mycosphaerella fijiensis (Mycosphaerellaceae) (2019)
ABSTRACT: Banana is one of the most important edible crops in the world, however, it’s attacked by different pathogens, one of the most prominent of these is the fungus Mycosphaerella fijiensis, causal agent of Black Sigatoka. The environmental and economic issues related to the pesticides used for its control have encouraged the search for cleaner alternative biomolecules. Previous studies were made by the Biotechnology group from the Universidad de Antioquia searching for a biological alternative for the control of M. fijiensis; in these the antifungal capacity of the fungus Ganoderma lucidum was determined as an antagonist and then as a source of protein extracts with inhibitory activity in vitro and in greenhouse plants; these findings were the foundation of this work, which focuses in the study of the enzymatic capacity of the proteins present in the protein extracts, due to their potential ability to degrade different compounds, including polysaccharides, lipids, peptides and nucleic acids, constituents of essential parts of a living cell; therefore these extracts can act as possible antifungal agents. In this study, protein extracts of G. lucidum obtained from bioreactor cultures (BIOFLO 110®) were characterized in terms of their deoxyribonuclease, ribonuclease, protease, glucanase and chitinase enzymatic activities. The extracts were also fractionated and each fraction obtained was evaluated for its inhibitory capacity against the phytopathogen fungus M. fijiensis, and through mass spectrometry analysis the presence of different enzymes with antifungal potential was confirmed.